An Appraisal of Local Content Legislation and Policies in Oil and Gas Producing Countries - Ebu, Alex Abang (dialektika kontemporer, 2024)
One of the aims of the local content policy (LCP) is the economic development of oil and gas producing countries through the utilization of local personnel and resources in the activities of oil and gas sector. Local content legislation and policies in oil and gas producing countries have become a key priority of host governments and industry players alike. Increasingly, more resource rich development countries are enacting local-content legislation as a means of maximizing the benefits to be gained from their petroleum industries. However, these laws and policies are being implemented with insufficient research into their efficacy, and as a result have often yielded mixed results. This paper examines the effect of local-content legislation and policies in the oil and gas industry presenting insights on the challenges faced by industry players with regard to their implementation. We traced the channels through which local-content legislation advances value creation by evaluating different implementation programmes, using clearly stated local-content targets to measure their efficacy. In this article, Nigeria, Ghana, Brazil and Norway are chosen as case study countries to highlight the diversity of local content strategies for countries at different developmental stages. The research adopts the doctrinal method, which is library-based involving the examination of primary and secondary source materials on this subject matter. The motivation for this study is to provide host governments, investors and domestic suppliers with guidelines on how to successfully develop and implement local-content regulations and strategies. The research findings from these case study countries aforementioned shows that the success or otherwise of local content legislation and policies remains a function of a country’s institutional setting and developmental paradigm. Based on the review of the case studies, we summarized that the successful local-content legislation and policies should be anchored on the following principles: local content policies need to look beyond simple generation of economic rents to focus on the development of linkages, the tools developed to measure agreed local content benchmarks must be clearly defined to the acceptance of all industry players, and entrenching local-content depends on the availability of an industrial-supply base that can act as growth levers.